Open innovation in embedded systems - Soeldner, Carsten-Constantin (Springer Gabler, 2017)
Carsten-Constantin Soeldner's investigation enables embedded systems firms to understand how they can open their systems to gain access to the ideas and solutions of external users and developers. Similar to smartphones with their large number of apps, firms are now beginning to open their embedded systems towards open innovation. Despite the large potential to increase innovativeness, firms face a variety of obstacles, such as the presence of safety and real-time constraints or the need to protect intellectual property. Carsten-Constantin Soeldner identified a variety of approaches how firms can still open their systems while not violating these constraints. The book is built on four different studies which comprehensively illuminate open innovation strategies for embedded systems. Contents Organizational and technical challenges Organizational forms of openness Technical forms of openness Approaches for the modularization of embedded systems for openness Unexpected open innovation, such as hacking Target Groups Researchers and students in the field of information systems, open innovation and embedded systems Practitioners in the field of innovation management, product management as well as in the design of embedded systems The Author Dr. Carsten-Constantin Soeldner was a research associate at the Chair of Information Systems I (Prof. Dr. Kathrin Möslein) at the Friedrich-Alexander-University of Erlangen-Nuremberg. He also serves as a Managing Director in a consulting company.
Keywords: Embedded computer systems.; elektronické knihy; electronic books